Organizational Becoming as Dialogic Imagination of Practice: The Case of the Indomitable Gauls - Carlsen, Arne (Organization Science, 2006)
This paper explores the relationship between authoring of identities and organizational development through a case study of the 18-year history of a professional service firm. Drawing from process theory, narrative psychology, and practice approaches to identity, I outline a perspective on organizational becoming as dialogic imagination of practice. Conceived as such, authoring takes place as a continuous stream of suggestions of what practice is, has been, and could be, simultaneously addressing life enrichment and organizational development. Three forms of imagination of practice are identified as central in the development of the case organization: (1) the instantiating of project experiences as identity exemplars; (2) a powerful dramatizing of trajectories of practice, exemplified by use of the metaphor of the “Indomitable Gauls;” and (3) a subsequent reframing instigated by discontinuous changes in dominant activity sets. The three authoring forms are discussed in relation to organizational development and adaptation. Implications include increased attention to forward-looking authoring motives and hope, a reformulation of the identity question from “who are we?” to “what are we doing?” and a possible location of practices as belonging to stories beyond that of the organization.